Facebook: Creación y usos de códigos comunicacionales por jóvenes del colegio Los Andes del cantón Píllaro. - Espejo Minta, Jesica Maribel (2018)
The development of the digital platforms has allowed young people to create and use different types of codes to communicate with other users. Virtual platforms offer to be tools for the communication of people, especially young people, who have greater participation within the social network like Facebook. The Internet is a technology that has an especial impact on teenagers and provid them different way to communicate with distant or close people. The objective of this research is to analyze how the young people from the Píllaro city create and use the new communication codes within the social network Facebook to establish if they have an impact on their language and spelling. To carry out the study, we worked with young people of both sex, between 15 and 18 years old, who attend the fourth, fifth and sixth year of the Los Andes School, belonging to the Píllaro city of Tungurahua province. In accordance with the specific objectives set out in the research, the methodology used were quantitative and qualitative nature. We work with the quantitative approach, through a survey to identify the codes used by young people and adolescents through social networks. Subsequently, the results will be analyzed and interpreted. In the same way, the qualitative approach will allow to make an observation sheet and an interview that will be applied to the students and teacher of the subject language and literature, to analyze the types of communication codes that the youth of the Los Andes School of the Píllaro city have created on the social network Facebook. Finally the students of the Los Andes School have representation in social networks, because through these tools they have used new codes that have been created with the purpose of making the message more fun, to communicate and relate. Through the internet, young people have proposed strategies to understand the codes and interpret them and get a clear and precise message. Young people used new codes communications for sending funny messages. Based on the analysis of the results, it was concluded that through the research it was possible to identify that the social network Facebook affects the spelling in a personal way in the students of the Los Andes School because 15 new codes (abbreviations) were found that the young people they use it daily in their publications. Likewise, it was shown that emojis are the main communication code that young people use as a fast and quick way to communicate with each other. This shows that visual language facilitates interaction between subjects over long distances.